STUDENTS' ERROR ANALYSIS IN COMPLETING TOEFL READING SECTION AT IAIN PAREPARE - Wahyu Pradana T; Kalsum Kalsum (Journal of English Education, 2026)
This study analyzed students' errors in completing the reading section of the TOEFL test at IAIN Parepare and identified the factors that influenced those errors. The research responded to the need to understand specific reading-test difficulties faced by English Education students, particularly because TOEFL scores are commonly used for academic requirements and language proficiency evaluation. A descriptive qualitative design was employed. The participants were 28 English Education students selected through random sampling. The instruments consisted of TOEFL reading-section documentation containing 50 items and an interview guide. The data were analyzed through reduction, display, conclusion drawing, and percentage calculation. The findings showed that students made errors across all TOEFL reading aspects: main idea questions (62.14%), definition from structural clues (58.93%), tone, purpose, and course questions (65.00%), implied detail questions (67.86%), transition questions (66.43%), stated detail questions (63.57%), unstated detail questions (69.64%), and pronoun reference questions (65.48%). The most dominant error appeared in unstated detail questions. Interview results indicated that time management, unfamiliar vocabulary, and lengthy reading passages were the major factors influencing students' errors. The study concludes that TOEFL reading preparation should strengthen vocabulary mastery, skimming-scanning skills, and timed reading practice.